Husstanden som kloster: ’Verdslig askese’ i dansk husholdnings- og bønnelitteratur efter reformationen - Thomsen, Søren Feldtfos (Religionsvidenskabeligt Tidsskrift, 2016)
In this article I explore the re-interpretation of asceticism in the Danish Protestant reformation of the sixteenth century. With Max Weber’s concept of ‘inner-worldly asceticism’ as my starting point, I analyze a number of printed Danish evangelical household manuals and prayer books from the post-reformation era, tracing the ascetic features of the ideal household as it was articulated by Lutheran devotional authors of the period. These features included a daily life punctuated by prayer and contemplation, an emphasis on obedience to paternal authority, the regulation of sexuality, and an understanding of manual labor as a form of divine service. Thus, I argue that the ascetic ideal of medieval monasticism persisted after the formal adoption of Lutheranism in Denmark and the abolition of the Danish monasteries, above all in the Lutheran ideal of the marital household.